Lineage Divergence of Dendrolimus punctatus in Southern China Based on Mitochondrial Genome - Du, Huicong; Liu, Man; Zhang, Sufang; Liu, Fu; Zhang, Zhen; Kong, Xiangbo (Frontiers in Genetics, 2020)
In southern China, the masson pine caterpillar, Dendrolimus punctatus, has caused serious damage to the Pinus massoniana (Lamb.) pine forests. Here, the whole mitochondrial DNA (mtDNA) was employed to analyze the population evolution of D. punctatus and to understand the process underlying its current phylogenetic pattern. D. punctatus populations within its distribution range in China were categorized into five subgroups: central and eastern China (CEC), southwestern China (SWC), Yibin in Sichuan (SC), Baise in Guangxi (GX), and Luoding in Guangdong (GD), with a high level of haplotype diversity and nucleotide diversity among them. The genetic distances between subgroups are relatively large; however, the genetic distances between populations within the CEC subgroup were relatively small, suggesting that many populations were closely related in this subgroup. The mantel test showed that geographic distance had an important impact on the genetic distance of different geographic populations (r = 0.3633, P < 0.001). The neutrality tests, Bayesian skyline plot, and haplotype network showed that D. punctatus experienced a population expansion around 100,000 years ago. The divergence times of GX/SC, SWC, GD, and CEC were 0.347, 0.236, 0.200, and 0.110 million years ago, respectively. The SWC, CEC, and GD subgroups might have evolved from GX or SC subgroups. The population genetic structure of D. punctatus was closely related to its host tree species, geographic distance among populations, the weak flight capacity, and many eco-environment conditions.